Analysis of the Accounting System of PT Sulsel Citra Indonesia to Support Managerial Decision-Making - Maharani, Ambia; Sumarlin, Abdul; Arsyad, Aisyah Tiar (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The increasingly dynamic development of the business world requires every company to have a reliable accounting system as the basis for quick and accurate manajerial decision-making. PT Sulsel Citra Indonesia is a company engaged in multiple businesses, including property management, nickel mining management, railway operations, parking management, hazardous waste transportation service, and culinary businesses. The community service activity aims to analyse the accounting system implemented at PT Sulsel Citra Indonesia and provide recommendations for improvement in order to enhance the effectiveness of the accounting information system in supporting managerial functions. The implementation methods include field observations, interviews with finance staff, and analysis.The results of the study show that financial information plays a very important role in supporting managerial decision-making, as well as a strong internal accounting standard procedure system to make the flow of financial information more efficient and accurate. The implementations is expected to improve the effectiveness of financial control and support a more strategic decision-making process in a multi-business corporate environmrnt. In general, optimal accounting practices not only help companies maintain financial stability, but also provide an important basis for more accurate decision-making and business sustainability.